A comparative immunohistochemistry study of diagnostic tools in salivary gland tumors: usefulness of mammaglobin, gross cystic disease fluid protein 15, and p63 cytoplasmic staining for the diagnosis of mammary analog secretory carcinoma?. (18th July 2014) - Projetti, Fabrice; Lacroix‐Triki, Magali; Serrano, Elie; Vergez, Sebastien; Herbault Barres, Béatrice; Meilleroux, Julie; Delisle, Marie‐Bernadette; Uro‐Coste, Emmanuelle
<x xml:space="preserve">Abstract</x> Background Mammary analog secretory carcinoma (MASC) of the salivary gland has been recently described according to morphological, immunohistochemical, and molecular (ETV6‐NTRK3 translocation) similarities with the mammary secretory carcinoma. The most important differential diagnostic considerations of MASC are low‐grade adenocarcinoma not otherwise specified (NOS), cystadenocarcinoma, and acinic cell carcinoma (AciCC). These tumors may share an overlapping morphology with MASC, and additional immunohistochemical studies are required to reinforce the diagnosis. Mammaglobin, GCDFP‐15, and p63 staining have been reported in MASC. Our study was designed to check the specificity of these antibodies in MASC compared to other frequent tumors of salivary glands. Methods A series of 62 salivary gland tumors [10 MASCs, 5 adenocarcinomas NOS and 2 cystadenocarcinomas with MASC features and without ETV6 rearrangement, one low‐grade cribriform cystadenocarcinoma (LGCCC), 9 AciCCs, 10 MECs, 10 adenoid cystic carcinomas (AdeCCs), 5 polymorphous low‐grade adenocarcinomas (PLGAs), and 10 pleomorphic adenomas (PAs)] was analyzed by immunohistochemistry with mammaglobin, GCDFP‐15, and p63 antibodies. Results Positivity for mammaglobin was observed in all MASCs, cystadenocarcinomas, LGCCC, and PLGAs, in some adenocarcinomas NOS, PAs, and MECs, rarely in AciCCs and never in AdeCCs. Positivity for GCDFP‐15 was observed in most of the tumor types except in AdeCCs. Interestingly, cytoplasmic positivity for p63 was observed in most of MASCs and PLGAs while rarely in adenocarcinomas NOS and PAs, and never in the other tumor types. Conclusion Our study revealed the usefulness of mammaglobin and p63 cytoplasmic staining to define which tumors are worth to be screened for ETV6 rearrangement.